Oblicza ezoteryzmu - Drozdowicz, Zbigniew (Humaniora. Czasopismo Internetowe, 2021)
Esoterism belongs to those phenomena present for a long time in culture which caused and still cause certain interest, as well different kinds of reservations and raise certain questions. The main issue is however made here by the fact that it had taken and still takes various forms and it is being perceived and presented differently by both - its followers and its academic researchers. In these remarks I will recall several exatmples of that. Although none of those researchers aren’t willing to marginalize and trivialize the issue they do differ in the judgment of its cultural impact. I’m willing in that matter to share the general thesis by saying that it had played and still does an alternative role to the socially dominant forms of culture.